NAIF1 suppresses osteosarcoma progression and is regulated by miR‐128. (8th November 2018) - Kong, Daliang; Zhang, Zhe
Abstract : Nuclear apoptosis‐inducing factor 1 (NAIF1) acts as an oncogene and involves in tumorigenesis in several cancers. However, the expression and mechanism of NAIF1 in osteosarcoma remains unclear. In this study, we demonstrated the downregulation of NAIF1 expression in both osteosarcoma tissues and cell lines. We next explored the potential role of NAIF1 in osteosarcoma cell proliferation and migration. The result showed that overexpression of NAIF1 evidently suppressed the cell proliferation and invasion of osteosarcoma. Furthermore, we investigated the potential mechanisms accounting for dysregulation of NAIF1 in osteosarcoma. The bioinformatic prediction and luciferase reporter assay revealed that miR‐128 is a direct upstream regulator of NAIF1 and regulates NAIF1 expression by binding the 3′‐UTR of NAIF1. Consistent with previous study, we found that miR‐128 was upregulated in both osteosarcoma tissues and cell lines. Moreover, miR‐128 expression levels were inversely correlated with that of NAIF1 in osteosarcoma tissues. Finally, functional assay showed that miR‐128 significantly suppressed osteosarcoma progression partially mediated by inhibiting NAIF1 expression. These data indicate that the miR‐128 and its target gene NAIF1 played important roles by regulating OS cell proliferation and migration phenotype. Significance of the study: Osteosarcoma (OS) is the most common malignant bone tumour and the second leading cause of cancer‐related death affecting children and adolescents. Nuclear apoptosis‐inducing factor 1 (NAIF1) plays an inhibitory role in the initial steps of different carcinomas. However, the expression and mechanism of NAIF1 in osteosarcoma remains unclear. The data of this study indicated that the miR‐128 and its target gene NAIF1 played important roles by regulating OS cell proliferation and migration phenotype. It was demonstrated that NAIF1 would demonstrate important regulative effects and may be a promising therapeutic target of OS.